2015
DOI: 10.1515/strm-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing model robustness via a distortion of the stochastic root: A Dirichlet prior approach

Abstract: It is standard in quantitative risk management to model a random vector

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The question can be answered by the following example: Define an exchangeable min-id sequence via the extended chronometer (H t ) t∈R = − log (1 − Γ t ), where (Γ t ) t∈R denotes a Dirichlet process, which can be seen as a prior distribution on random distribution functions in a Bayesian framework [12]. The authors of [37] have shown that H is indeed infinitely divisible, which implies that the associated exchangeable sequence X is min-id. Moreover, [37] show that the upper and lower bivariate tail dependence coefficients ρ u 2 and ρ l 2 of X can take any value in (0, 1) Thus, exchangeable min-id sequences can exhibit arbitrary positive bivariate upper and lower tail dependence, which shows that the dependence structure of exchangeable min-id sequences is much richer than the dependence structure of exchangeable min-stable sequences.…”
Section: Main Results: Linking Exchangeable Min-id Sequences To Exten...mentioning
confidence: 99%
See 1 more Smart Citation
“…The question can be answered by the following example: Define an exchangeable min-id sequence via the extended chronometer (H t ) t∈R = − log (1 − Γ t ), where (Γ t ) t∈R denotes a Dirichlet process, which can be seen as a prior distribution on random distribution functions in a Bayesian framework [12]. The authors of [37] have shown that H is indeed infinitely divisible, which implies that the associated exchangeable sequence X is min-id. Moreover, [37] show that the upper and lower bivariate tail dependence coefficients ρ u 2 and ρ l 2 of X can take any value in (0, 1) Thus, exchangeable min-id sequences can exhibit arbitrary positive bivariate upper and lower tail dependence, which shows that the dependence structure of exchangeable min-id sequences is much richer than the dependence structure of exchangeable min-stable sequences.…”
Section: Main Results: Linking Exchangeable Min-id Sequences To Exten...mentioning
confidence: 99%
“…The authors of [37] have shown that H is indeed infinitely divisible, which implies that the associated exchangeable sequence X is min-id. Moreover, [37] show that the upper and lower bivariate tail dependence coefficients ρ u 2 and ρ l 2 of X can take any value in (0, 1) Thus, exchangeable min-id sequences can exhibit arbitrary positive bivariate upper and lower tail dependence, which shows that the dependence structure of exchangeable min-id sequences is much richer than the dependence structure of exchangeable min-stable sequences.…”
Section: Main Results: Linking Exchangeable Min-id Sequences To Exten...mentioning
confidence: 99%
“…in probability forecasting (Dawid, 1984)), but, to our knowledge, has not been utilised in the context of sensitivity analysis. Nonetheless, there are some conceptual parallels of our work with Mara and Tarantola (2012), who consider multivariate normal variables in a variance-based sensitivity framework, Mai et al (2015), who study model robustness via a transformation of the input vector, and Kraus and Czado (2017), who carry out bank stress testing using graphical dependence models.…”
Section: Relation To Existing Literaturementioning
confidence: 98%
“…This is [61,Theorem 3.5]. In order to prove necessity, the principle of inclusion and exclusion can be used to express the survival copula of Ĉ as an alternating sum of lower-dimensional margins of Ĉ.…”
Section: The Dirichlet Prior and Radial Symmetrymentioning
confidence: 99%